SPEECH STYLE USED BY THE MAIN CHARACTERS IN HIDDEN FIGURES MOVIE - Nickita, Debby Sarah; Fadilah, Eka; Kurniawan, Yulius (Universitas Widya Kartika Surabaya, 2023)
The purpose of this study was to analyze the types of speech styles used by the main characters in the Hidden Figures movie and the factors governing the use of specific speech style. According to Joos (1967) there are five types of speech styles; frozen, formal, consultative, casual, and intimate. The study only focuses on the conversation between the main characters with colleagues and family. The descriptive qualitative approach proposed by Ary et al (2010) was used in this research. The data considered for the study was the movie’s subtitles. Hereafter, the utterances classified based on their features of speech styles. The present study found that five types of speech styles have been used in the film. The most used speech styles are formal and casual. The factors govern the use of certain speech styles are the following: the social background of the addressee, speech convergence, and age of the addressee.